Effect of watering frequencies on water intake and drinking behaviour of Surti goats - R. J. MODI and K. N. WADHWANI, ARUNA PATEL, N. R. PATEL (Indian Journal of Animal Production and Management, 2020)
The present experiment was conducted to study the effect of different watering frequencies on water intakeand drinking behaviour of Surti goats under intensive production system during hot dry and hot humidseason. Eighteen adult farm born dry non pregnant female Surti goats (20 - 30 kg) were divided randomlyon the basis of body weight comprising of six animals in each treatment viz., T1: Control (watering thrice aday), T2: (12 hrs watering interval – watering twice a day), T3: (24 hrs watering interval – watering once aday). The water intake and total water intake time (sec.) of experimental animals were significantly (P < 0.05)influenced by different watering frequencies and seasons. Moreover, rehydration influenced significantly (P< 0.05) the water intake and drinking behaviour in terms of total water intake time (sec.) and water intake(ml/sec.) of goat. The results indicated that the adult goat should be given ad libitum water at least twicea day to maximize water intake in hot dry and hot humid season.